Efficient electrosynthesis of dimethyl carbonate from urea and methanol under mild conditions. Issue 3 (18th January 2023) - Sun, Mingjuan; Li, Fengjiao; Cui, Yanhui; Zhao, Xiaolin; Chen, Haiwei; Liang, Shuting
Abstract : Mild and efficient synthesis of DMC has been successfully performed by electrolyzing low-cost and abundant urea and methanol. Abstract : Dimethyl carbonate (DMC) has versatile applications in chemical, pharmaceutical, and new energy industries. Synthesis of DMC from low-cost and abundant urea and methanol is an attractive and promising strategy via indirect utilization of CO2 . However, high temperature and pressure are usually required for the thermo-synthesis of DMC from urea and methanol. Herein, mild and efficient synthesis of DMC has been firstly developed by electrolyzing urea and methanol over Pt (+)|Ti (−) electrodes in an undivided cell. Effects of various electrosynthesis conditions, supporting electrolytes, and electrode materials were systematically investigated. Under optimized conditions, the highest DMC yield of 50.4% with 100% selectivity was achieved. Furthermore, a possible mechanism was proposed for the electrosynthesis of DMC from urea and methanol. Other important organic carbonates such as diethyl carbonate (DEC), dipropyl carbonate (DPC), dibutyl carbonate (DBC), ethylene carbonate (EC), and propylene carbonate (PC) were also successfully synthesized by this mild electrosynthesis method.